Classification of Cybercrimes in GCC Countries - Dmitrievna Tsyplakova, Alyona; Anatolyevich Shestak, Viktor (Law, State and Telecommunications Review, 2024)
[Purpose] For the time being, one of the most cyber resilient countries not only in the Middle East, but worldwide is Kingdom of Saudi Arabia alongside with the United Arab Emirates that pioneered the criminalization of computer-related offences. The question is what country has evolved enough thought years and may set an example in order to reform other Arab legislation. [Methodology/Approach/Design] This study is a description investigation of cybercrimes in the Kingdom of Saudi Arabia, the United Arab Emirates, the Kingdom of Bahrain, the Sultanate of Oman, the State of Qatar and the State of Kuwait mainly based on genetic, systematic-functional and systematization methods. Data on features of translation, as well as legal framework of GCC members and comparison of provisions of the Budapest convention on cybercrime and the Arab convention on combatting information technology offences summarized in Tables. [Findings] Not only does the terminology in Arab states vary from conventional approach, but the structure and categories are atypical in contrast to international documents such as the Budapest convention on cybercrime. Since there is no unity within even 6 members of Gulf Cooperation Council, it calls for harmonization and either update of the Arab Convention on combating information technology offences or implementing the GCC Model Law (Riyad Document).